A left ventricular assist device interfering with leadless pacemaker implantation. Issue 11 (12th August 2021) - Smietana, Jeffrey; Schell, Andrea; Pothineni, Naga Venkata K; Walsh, Katie; Lin, David
Abstract: Left ventricular assist devices (LVAD) produce electromagnetic interference (EMI) which can have implications when patients require cardiac implantable electronic devices. Leadless pacemakers have been successfully implanted in patients with Heartmate 2 and Heartmate 3 LVADs without evidence of EMI or device‐to‐device interaction. Here we report a case of a Heartmate 3 LVAD and Micra VR transcatheter pacing system interaction requiring device repositioning.